2008
DOI: 10.1186/1758-2652-11-s1-p10
|View full text |Cite
|
Sign up to set email alerts
|

Immune restoration during HAART: 8-year follow-up in HIV-positive patients with sustained virological suppression

Abstract: Durable virological suppression during HAART is associated with immunological recovery in patients with HIV infection. Current guidelines recommend to initiate HAART when CD4+ cell count falls <350/μl. However, recent studies have shown a higher immune restoration when HAART was started at CD4+ baseline level > 350 cells/μl. We retrospectively assessed the long-term immunological outcome in patients with sustained virological suppression during HAART, for up to 8 years. MethodsHIV-infected consecutive patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Although, it varies in different settings, ART should be started when CD4+ count is 201-350, or <= 200/µl for developed and resource-poor settings, respectively (21). However, given the observed lower morbidity, mortality and fewer adverse events associated with the initiation of HAART at higher CD4 cell counts (23,24), WHO recommends CD4+ count <= 350 cells/µl to initiate ART as a universal guideline (5).…”
Section: Monitoring Of Treatment Responses In Patients On Haartmentioning
confidence: 99%
See 3 more Smart Citations
“…Although, it varies in different settings, ART should be started when CD4+ count is 201-350, or <= 200/µl for developed and resource-poor settings, respectively (21). However, given the observed lower morbidity, mortality and fewer adverse events associated with the initiation of HAART at higher CD4 cell counts (23,24), WHO recommends CD4+ count <= 350 cells/µl to initiate ART as a universal guideline (5).…”
Section: Monitoring Of Treatment Responses In Patients On Haartmentioning
confidence: 99%
“…Overall, the long-term shape of CD4+ count after HAART depends on the baseline CD4+ count, control of viral replication overtime, the stage of the disease at baseline, duration on treatment (39,40), as well as on baseline patient factors including higher HIV RNA level, co-morbidities, presence of drug resistant viruses, sub-optimal pharmacokinetics, and potency of the ARV regimen (17). The time required to reach to normal value of CD4+ counts ranges from two to eight years (24,41).…”
Section: The Profile Of Immunologic and Virologic Responses To Haart mentioning
confidence: 99%
See 2 more Smart Citations
“…However, there are patients who show an early CD4 cell recovery even with positive plasma HIV viral load, while others have a slow CD4 cell gain in spite of having a long‐term suppressed HIV viral load. The mechanisms underlying this immunovirological discordance are not fully understood . Some studies have shown that efficient thymopoiesis is key to the natural maintenance and ART‐mediated recovery of naïve and total CD4 cell counts in HIV‐infected individuals .…”
Section: Introductionmentioning
confidence: 99%